Modulation of destructive quantum interference by bridge groups in truxene-based single-molecule junctions. Issue 5 (21st December 2020) - Wang, Lin; Zhao, Zhihao; Shinde, Digambar B.; Lai, Zhiping; Wang, Dong
Abstract : Nitrogen and carbonyl bridge substituents embedded in truxene derivatives enhance the single-molecule conductance prominently by alleviating the destructive quantum interference effect and pushing away the anti-resonance dip from the Fermi energy. Abstract : Electron transport properties of polycyclic truxene derivatives have been investigated by the single molecule conductance measurement technique and theoretical study. Molecules with nitrogen and carbonyl substituents at the bridge sites exhibit higher single-molecule conductances by almost one order of magnitude compared with non-substituted analogues. It can be ascribed that the anti-resonance feature produced by destructive quantum interference (DQI) is alleviated and pushed away from the Fermi energy. These findings provide an effective chemical strategy for manipulating the DQI behavior in single molecular devices.